1678a The long history of agriculture and occupational disease in ireland. (24th April 2018) - Hayes, J
Abstract : Since man arrived to Ireland agriculture has been integral to the political cultural and economic development of our society. Indeed our principal mythology involves a row over a prize bull. Early settlers probably came from northern Spain or southern France some 10, 000 years ago and were hunter gatherers. Early evidence shows increased deforestation with cereal growing mainly oats and barley. Although some settlements developed in proximity to Christian monasteries, urbanisation came with the Vikings in medieval times. Significant geopolitical change did not occur until the 18th century with the collapse of the Celtic society. With the plantations came the development of modern agriculture in Ireland. Industrialisation, with the exception of the northeast, did not occur in Ireland. Agricultural developments saw flax in Ulster, tillage in Leinster and dairying in Munster. However whether freehold or tenant 50% of holdings in the early 1800s were between one and five acres. With increasing need to sell product tenant, farmers became dependent on the potato for sustenance and on the 'lumper' in particular. By the 1840s, the population had increased to 8 million. The famine of the 1840s due to failure of the potato crop resulted in significant death and emigration. In the twentieth century holdings increased in size with the focus on dairy and beef. Agricultural related industries such as brewing, sugar production and flour production continued. The utilisation of peat for the development of turf-related industries occurred in the twentieth century. Currently, the emphasis on the whole island remains on dairy and beef production. Improvement in regulation through the European Union has resulted in fewer farm accidents, reduction in respiratory and dermatological conditions The agrifood sector accounts for 10% of employment today. Holding remains small and part time farming is common.